2011
DOI: 10.1259/dmfr/35578628
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of the bony nasal pyramid dimensions in Anatolian people

Abstract: Objectives: The aim of this study was to evaluate the nasal bone and bony nasal pyramid in adult Anatolian people. Method: A total of 80 patients (48 males, 32 females, mean age of 40.03 years) were all evaluated using CT. Upper, intermediate and inferior thickness of the nasal bone on each side and on the lateral and medial osteotomy line were measured. In addition, nasal bone length and pyriform aperture width were determined. Conclusion:The dimensions of the nasal pyramid are known to be important in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The width (PA-W) was wider than the Turks (Table IV) (Yüzbasioglu et al,), Korean, Caucasian, German, Austrian, Anatolian and American results, and smaller than in black people (Table IV) (Lang & Baumeister, 1982, obtained from the study by Hwang et al;Hoffman et al, 1991;Ofidile, 1994;Hommerich & Riegel, 2002;Karadag et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The width (PA-W) was wider than the Turks (Table IV) (Yüzbasioglu et al,), Korean, Caucasian, German, Austrian, Anatolian and American results, and smaller than in black people (Table IV) (Lang & Baumeister, 1982, obtained from the study by Hwang et al;Hoffman et al, 1991;Ofidile, 1994;Hommerich & Riegel, 2002;Karadag et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…It can decide the most effective procedure, for example: osteotomies (Prokop, 2000;Karadag et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…So, excess soft tissue changes needs wider and circular PA. With respect to shape of the piriform aperture, in Boyan study type II was predominant (51.8%), followed by type I (25.0%) and then types IV and III with similar frequency (12.5% and 10.7%, respectively) [3]. According to Ofodile, the shape of the piriform aperture was oval (equivalent to types III and IV) in Ashanti, triangular (type II) in Austrians and American Indians, and varied from oval to triangular in black Americans (type III) [10]. It was observed that the most common was the type I (pear -39.1 %) and the less common were type III (diamond -0.0 %), type II (inverted heart -1.6 %) and type IV (inverted heart -3.1 %) [15].…”
Section: Methodsmentioning
confidence: 97%
“…The lateral border articulates to the frontal process of the maxilla. [3,[7][8][9] Inferiorly, the PA is the large opening in the nasal region and the anterior opening of the nasal cavity. It is bounded superiorly by the nasal bones and laterally and inferiorly by each maxilla.…”
Section: Anatomy Of Pamentioning
confidence: 99%
“…This morphological variability is necessary to understand the geographic and ethnic differences and can be analyzed by radiography in forensic context. [2,5,7] In addition to forensic implications, the knowledge of the PA and nasal bone variations is fundamentally significant in anthropology and otolaryngology. [2] The present review gives a brief outline of the forensic value of PA.…”
Section: Introductionmentioning
confidence: 99%